Accreditation of Experiential Learning From Personal Initiative to Supervised Realization an Experiment at Bordeaux 1 University - Sand, I.; Duchamp, G. (Elektronika ir Elektrotechnika, 2010)
AEL (VAE in French) was set up at the University of Bordeaux 1 in accordance with the provisions of the law of social moderniza-tion of January 17, 2002. After a brief rundown on the legislative framework and the local context, the article focuses on the role of the actors involved in a series of meetings with the applicant - steps giving the AEL procedure its pedagogical dimension. It highlights the approach at Bordeaux 1, as to those aspects in the procedure which depend on the choice and initiative of the universities themselves. Through current experimentation, this article also presents the effects of such a procedure on the academic contents and teaching me-thods used in our university. Finally, we shall complete this presentation by assessing the procedure and indicating the stakes for the future.